From the field - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
These photos have been taken from the field and nature. You are free to share and copy these images, as long as it is for non-commercial work on agriculture, food security, forests, climate change and a like. Please credit the photographer and program. Photos: C.Schubert (CCAFS)